2010
DOI: 10.1364/josab.27.002416
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic gain switching in optically injected quantum dot laser lasing simultaneously from the ground and excited state

Abstract: International audienceWe analyze theoretically nonlinear dynamics of an optically injected two-mode quantum dot laser lasing simultaneously from the ground and excited states. We show that although the external optical signal is injected into the ground-state mode alone, it can lead to the generation of regular picosecond pulses and pulse packages in the intensity of the excited-state mode. Generation of regular streams of picosecond pulses is attributed to an intrinsic gain switching mechanism where the relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…1 of Ref. [21]. However introducing an asymmetry between the electron and the hole dynamics as described by Viktorov et al [12] allows to reproduce this behavior.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…1 of Ref. [21]. However introducing an asymmetry between the electron and the hole dynamics as described by Viktorov et al [12] allows to reproduce this behavior.…”
Section: Introductionmentioning
confidence: 94%
“…Recently some of us demonstrated that the characteristics of the first excited state (lasing or not) can have a major impact on the dynamics of optically injected QD lasers [20], [21]. Indeed the intraband relaxation time from the ES to the GS can enlarge or reduce the locking region, modifying the excitability characteristics of the system [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3(f)) is obtained. These two changes easily satisfy (5) and therefore reduce GS round trip cavity losses; this effect becomes stronger at larger current since ES power becomes larger. Therefore, when the current is sufficiently high, GS lasing turns on.…”
Section: A Lasing Regime Discussionmentioning
confidence: 97%
“…7 Abusaa et al 8 introduced a rate equation model which reproduces this behaviour and also shows that the intradot timescales strongly affect relaxation times in such lasers. Olejniczak et al 9 performed a theoretical study of optical injection in QD lasers lasing simultaneously from the GS and the ES, showing some interesting features including generation of picosecond pulses.…”
Section: Introductionmentioning
confidence: 99%